2022
DOI: 10.3389/fmicb.2022.756209
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Co-occurrence Network and Fermentation Information of Natural Woody-Plant Silage Prepared With Grass and Crop By-Product in Southern Africa

Abstract: To facilitate the use of woody plant (WP) as a natural biomass resource to address the shortage of feed for ruminants in the tropics, we use PacBio SMRT sequencing to explore the microbial co-occurrence network and silage fermentation of gliricidia and leucaena prepared with Napier grass (NG) and corn stover (CS) in Southern Africa. Based on dry matter, the crude protein contents of WP are as high as 25%. Compared with NG, the addition of CS speed up the dynamic succession of microorganisms in the silage ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Ensiling without the use of an inoculant or starter is a spontaneous fermentative process in which fermentation mainly depends on the composition of epiphytic microorganisms and the natural occurrence of epiphytic LAB ( Guo et al, 2018 ). Many studies have shown that by using the PacBio SMRT sequencing, microorganism composition and its dynamics in the ensiling process can be precisely revealed at the species level because it can generate long sequence reads, which provides valuable biological information regarding the complete bacterial community in the ensiling system ( Bai et al, 2021 ; Du et al, 2022a , b ). The bacteria in all samples of fresh and silage ryegrass in this study were sequenced by SMRT sequencing technology to accurately assess the microbial community and diversity ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensiling without the use of an inoculant or starter is a spontaneous fermentative process in which fermentation mainly depends on the composition of epiphytic microorganisms and the natural occurrence of epiphytic LAB ( Guo et al, 2018 ). Many studies have shown that by using the PacBio SMRT sequencing, microorganism composition and its dynamics in the ensiling process can be precisely revealed at the species level because it can generate long sequence reads, which provides valuable biological information regarding the complete bacterial community in the ensiling system ( Bai et al, 2021 ; Du et al, 2022a , b ). The bacteria in all samples of fresh and silage ryegrass in this study were sequenced by SMRT sequencing technology to accurately assess the microbial community and diversity ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in this study, compared with the BK group, the relative abundance of Enterococcus in CK and AK silages was higher, so the lactic acid content of CK and AK was lower than that of BK. Since Enterococcus are not acid-resistant genera and the pH value of BK was lower, there were few Enterococcus species in BK, and these were mostly Lactiplantibacillus plantarum , which were found to be more acid tolerant ( Du et al, 2022b ). In addition, more butyric acid and NH 3 -N accumulation in BK may have been due to higher protein content in the second ryegrass crop resulting in a higher protein degradation rate.…”
Section: Discussionmentioning
confidence: 99%
“…( Du et al, 2020 ). The utilization of fermentation substrates by LAB is limited ( Bai et al, 2020 ), and excess fermentation substrate may allow some unfavorable microorganisms with strong tolerance (such as acid tolerance and facultative anaerobic activity) to multiply or remain latent ( Wang et al, 2019a ; Yan et al, 2019 ; Du et al, 2022 ), which also partially explains the higher microbial diversity in NA3 and NA9 ( Figure 2 ). In this study, the treatment that was neither inoculated with LAB nor supplemented with corn flour (NA) had a high pH and low LA content.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, these complex microbial structures and interactions have been well characterized thanks to the single-molecule real-time (SMRT) technology that can cover full-length DNA fragments integrated on the PacBio platform. SMRT technology is also widely used to reveal the microbial environment of silage such as whole-plant corn, alfalfa, Napier grass, and sugarcane due to its high throughput, low error rate, and ability to trace microorganisms to the species or even strain level ( Cai et al, 2020 ; Bai J. et al, 2021 ; Xu D. et al, 2021 ; Du et al, 2022 ). To the best of our knowledge, so far, no studies revealing complete microbial information containing whole-plant paper mulberry silage have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Silage has the advantages of a strong sour taste and a moist and soft texture, which can improve its palatability to ruminants [13][14][15]. In addition, silage that can be stored can ensure a balanced supply of feed throughout the year and solve the problem of seasonal feed shortages in tropical regions.…”
Section: Introductionmentioning
confidence: 99%